OPALS: The Oxford plasma accelerator light source project - Bajlekov, S; Bartolini, R; Delerue, N; Doucas, G; Hooker, S; Peach, K; Urner, D; Wark, J (2008)
Recent progress in Laser Plasma Accelerators has demonstrated the possibility of generating GeV electron bunches with very interesting beam qualities. It is now conceivable that the further development of such devices could generate beams with emittance, energy spread and peak current suitable for FEL operation in the XUV range with relatively short undulator trains. In this context the OPALS project aims at the construction of a XUV radiation source, driven by a Laser Plasma Accelerator, capable of generating ultrashort fs XUV pulses. Such a source is small enough to be hosted in an academic or industrial institution and could therefore have a major impact on time-resolved science.